P650 IBD care from the patient perspective: The patient's turn. (21st January 2022) - Creemers, R; van der Horst, D; Raats, I; Romberg-Camps, M; Scherpenzeel, M; van Bodegraven, A
Abstract: Background: There is an increased focus on patient reported outcomes and patient reported experiences as means to optimize provided care. Both are considered essential in improving quality and service. Zuyderland Medical Centre (ZMC) is transforming its inflammatory bowel disease (IBD) care into a patient oriented IBD Centre (PGC IBD) as a way to provide modern patient centred care. The project 'Patient aan zet' is an initiative of Crohn & Colitis NL (CCNL) and takes place in several hospitals. The aim of the project is to optimize quality of care for adult patients with IBD by ensuring that the patient is properly and unambiguously informed and the patients involvement increases in treatment. Methods: A cross-sectional survey using a questionnaire was performed to map out expectations and experiences of patients with the IBD outpatient clinic of ZMC. This questionnaire (part of the project 'Patient aan zet') was developed by CCNL as an online self-completion instrument. The results of this questionnaire were assessed in a subsequent discussion group. All IBD-patients presenting for an outpatient appointment at ZMC in March 2021, received an e-mail with a link to the questionnaire. In total, 500 e-mails were sent. After completing the questionnaire, patients were given the opportunity to sign up for a discussion group. Results: In total, 198 participants completed the questionnaire fully or partially (40%) (Table 1). We found patients were satisfied with health care in general and with the information supply concerning IBD specifically. Use of the online monitoring tool MyIBDCoach and response time in the online monitoring tool contributed to positive judgment. In the discussion group emerged that continued attention must be paid to the impact of endoscopic procedures from the patient perspective as endoscopic procedures (as part of the mucosal healing concept) may induce lasting and major impact on patients disease experience. In line with the ongoing corona pandemic developments, patient prefer a combination of check-up appointments by phone and at the outpatient clinic depending on (burden of) disease activity. Finally, specific attention is necessary for patients with a longstanding disease history. Needs concerning dietary advice and psychosocial support appear to vary over time. Conclusion: ZMC is transforming its IBD care into a PGC IBD as a way to provide optimal and patient centred care. Involving patient in this process has given direction to optimizing patient information and patient involvement. The experiences gained from this process will be used to evaluate the PGC IBD after implementation and, together with the patient association, to develop a PREM that can be used to optimize IBD care.